1999
DOI: 10.1172/jci7453
|View full text |Cite
|
Sign up to set email alerts
|

A PDZ-interacting domain in CFTR is an apical membrane polarization signal

Abstract: Polarization of the cystic fibrosis transmembrane conductance regulator (CFTR), a cAMP-activated chloride channel, to the apical plasma membrane of epithelial cells is critical for vectorial transport of chloride in a variety of epithelia, including the airway, pancreas, intestine, and kidney. However, the motifs that localize CFTR to the apical membrane are unknown. We report that the last 3 amino acids in the COOH-terminus of CFTR (T-R-L) comprise a PDZ-interacting domain that is required for the polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
232
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(243 citation statements)
references
References 45 publications
8
232
3
Order By: Relevance
“…In other expression studies, EBP50 has been implicated in directly modifying CFTR Cl Ϫ channel activity 45 and directing the cellular distribution of CFTR. 46 Consequently, it will be important to further characterize the effects of PDZ1 expression on the location and function of CFTR as well as other cAMP-regulated anion channels.…”
Section: Discussionmentioning
confidence: 99%
“…In other expression studies, EBP50 has been implicated in directly modifying CFTR Cl Ϫ channel activity 45 and directing the cellular distribution of CFTR. 46 Consequently, it will be important to further characterize the effects of PDZ1 expression on the location and function of CFTR as well as other cAMP-regulated anion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids-Plasmids containing GFP-Myosin VI globular tail (GFPMyoVI-Tail), wt-CFTR (CFTR), and GFP-wt-CFTR (GFP-CFTR) constructs were generated as described (41,51). The GFP-CFTR Y/A LL/AA construct was generated from GFP-CFTR by the following alanine substitutions that disrupt the tyrosine and dileucine endocytic motifs, Y1424A, L1430A, and L1431A, using site-directed mutagenesis as described (52).…”
Section: Methodsmentioning
confidence: 99%
“…However, two other reports point to the possibility of C-terminal determinants. Apical routing of CFTR involves an interaction with a PDZ scaffolding protein that is mediated by a PDZ interaction motif at the C-terminus of CFTR (Moyer et al, 1999). Recently, MRP2 was also determined to have a functional PDZ interaction motif ('TKF') at its extreme C-terminus, as indicated by yeast two-hybrid and in vitro overlay assays (Kocher et al, 1999;Hegedus et al, 2003), and deletion or mutation of this sequence in MRP2-GFP was reported to confer basolateral localization in transfected MDCK cells (Harris et al, 2001).…”
Section: Mrp2mentioning
confidence: 99%